A simple algorithm for distance estimation without radar and stereo vision based on the bionic principle of bee eyes; IOP Conference Series: Materials Science and Engineering; Vol. 177 : Mechanical Engineering, Automation and Control Systems (MEACS 2016) - Khamukhin A. A. Aleksandr Anatolievich (Information technologies in Mechanical Engineering, 2017)
Title screen